The Use of KPI in Group Decision Support Model of ICT Projects Performance Evaluation - Herri Setiawan; Jazi Eko Istiyanto; Retantyo Wardoyo; Purwo Santoso (IAES Indonesia Section, 2015)
This paper proposes The Use of KPI in Group Decision Support System Model of ICT Projects Evaluation at Local Government Agency in Indonesia. This study is a part of the attempt to improve local government performance in Indonesia, especially for Local Government Agencies (SKPD) involved in Decision Support System (SPK), which should be optimized through Information Technology. Different from the prior research, in this paper we try to describe how to determine KPI in an ICT project at local government agency and the applicable evaluation model. Generally, this paper will discuss how to make an performance indicator, so that the output of an ICT project product can result the expected outcome, benefit, and impact. Furthermore, it will be explained in regard to the Group Decision Support System (GDSS) evaluation model by considering the applicable legislation aspect, which facilitates decision makers such as: Government Institution Executives, ICT Managers Unit, Business Process Owner Unit, and Society represented by Regional House of Representative, to give assessment or evaluation upon the implementation of ICT Projects at Local Government Agency. As the research support, survey and interview have been conducted to stakeholders in decision-making. The proposed model is expected to be able to give ideas and solutions in evaluating ICT Projects done at local government agencies in Indonesia.